Making A Mark: Wits School of Construction Economics and Management and Its Contribution to the Construction and Property Fields - Laryea, Samuel (University of the Witwatersrand, Johannesburg, 2025)
This book is a historical account on the Wits School of Construction Economics and Management, its contributions and impact in society, which is very significant and leaves a positive impression of academic and industry development, despite historical hurdles. It looks at the past, present, and future of the School in the broader context of South African history and the overall development of the university. The process of writing this book has been both challenging and exciting with interesting discoveries about the academic disciplines and the growth trajectory of the School. It was challenging uncovering information from various sources within the university and external sources. It has also been an interesting process learning about the rich history and contributions of a key School within the university to the South African and global society. This book chronicles the careers of some graduates of the School who served in the highest leadership and management roles, and made an indelible mark in the construction industry locally and internationally. The School’s graduates have made substantial contributions to the growth and advancement of the South African construction and property sectors and their respective statutory councils including the South African Council for Quantity Surveying Profession (SACQSP), South African Council for Project and Construction Management Professions (SACPCMP) and the South African Council for the Property Valuers Profession (SACPVP). The School’s graduates have also played leading roles in major construction firms that have built some of the iconic buildings in South Africa and other parts of the world. In recent years, many of the School’s graduates are increasingly being recruited by firms in Europe, Middle East, Australia, and the US, indicating the quality of their education and their value to employers and the global construction industry.
This book is submitted to the Faculty of Engineering and the Built Environment, School of Construction Economics and Management, at the University of the Witwatersrand, Johannesburg, 2025.
Keywords: Diversity; Equity; Inclusion; Transforming the undergraduate curriculum; Improving the impact of our research and innovation; Digitalisation of administration; SDG-9: Industry, innovation and infrastructure; SDG-11: Sustainable cities and communities